2019
DOI: 10.1038/s41598-019-40071-1
|View full text |Cite
|
Sign up to set email alerts
|

Vector uncoating limits adeno-associated viral vector-mediated transduction of human dendritic cells and vector immunogenicity

Abstract: AAV vectors poorly transduce Dendritic cells (DC), a feature invoked to explain AAV’s low immunogenicity. However, the reason for this non-permissiveness remained elusive. Here, we performed an in-depth analysis using human monocyte-derived immature DC (iDC) as model. iDC internalized AAV vectors of various serotypes, but even the most efficient serotype failed to transduce iDC above background. Since AAV vectors reached the cell nucleus, we hypothesized that AAV’s intracellular processing occurs suboptimal. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 63 publications
2
63
0
Order By: Relevance
“…For example, AAV4 was the most abundant variant in T cells at the DNA level, but its relative expression at the RNA level in those cells was very low, implying that this serotype may be inefficient at one or multiple steps the vector must complete between cell entry and triggering transgene expression. While it has been previously shown that barriers such as inefficient nuclear translocation, 46 nuclear uncoating, 47,48 and second-strand synthesis/transcriptional regulation by the capsid 49 can affect function of AAV vectors, it was interesting and unexpected that a vector capable of such efficient cell entry was so inefficient at transgene expression. These results position AAV4 as a powerful genetic tool to study AAV biology and the interactions between AAV and human T cells.…”
Section: Aav2retromentioning
confidence: 99%
“…For example, AAV4 was the most abundant variant in T cells at the DNA level, but its relative expression at the RNA level in those cells was very low, implying that this serotype may be inefficient at one or multiple steps the vector must complete between cell entry and triggering transgene expression. While it has been previously shown that barriers such as inefficient nuclear translocation, 46 nuclear uncoating, 47,48 and second-strand synthesis/transcriptional regulation by the capsid 49 can affect function of AAV vectors, it was interesting and unexpected that a vector capable of such efficient cell entry was so inefficient at transgene expression. These results position AAV4 as a powerful genetic tool to study AAV biology and the interactions between AAV and human T cells.…”
Section: Aav2retromentioning
confidence: 99%
“…Once located within the nucleus, AAV2 was found to accumulate in the nucleoli in an intact infectious state [ 55 ]. The mechanism of AAV uncoating is largely unknown and seems to be a limiting step during AAV transduction [ 56 , 57 ]. Both wildtype (wt) AAV as well as rAAV can integrate into the host genome [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides RGD4c, a portfolio of AAV targeting vectors are nowadays available for improved transduction of endothelial cells (reviewed in [ 10 , 62 , 63 ] and Table 2 ), some of which are also functional in the context of quiescent endothelial cells or endothelial progenitor cells which are discussed as tools for realizing “Trojan horse” concepts [ 81 ]. Moreover, for DC [ 83 ] and T cells [ 56 ] targeting AAV vectors are available.…”
Section: Adeno-associated Virus and Aav Vector Technologymentioning
confidence: 99%
“…These candidates are then produced as viral vectors and comprehensively characterized regarding production yield, efficiency, specificity and immune escape capabilities prior to application. In addition, these novel variants can be used as tools to identify the nature of barrier/s that impair transduction by the parental serotypes thereby adding to the understanding of the host-AAV interaction [ 81 , 83 ]. Finally, strategies are available to map the targeted receptors [ 85 ].…”
Section: Adeno-associated Virus and Aav Vector Technologymentioning
confidence: 99%